Respuesta :

Answer:

x = -1

y = 8

Step-by-step explanation:

y = -3x +5 . (1)

2x+y=6 .  (2)

(1) in (2)

2x + ( -3x + 5 ) =6

= 2x - 3x + 5 = 6

= -x + 5 = 6

Subtract 5 from each side

= -x = 1

x = -1

Now  put "-1" in for "x" in the first equation:

y = -3 (-1) +5

= y = 3 + 5

= y = 8

Hope that helps!

:D

981083

Answer:

Step-by-step explanation:

Graph the line using the slope and y-intercept, or two points.

Slope:

3

-

3

y-intercept:

(

0

,

5

)

(

0

,

5

)

x

y

0

5

5

3

0

ACCESS MORE